How Do the CEO Political Leanings Affect REIT Business Decisions?. Issue 4 (14th December 2021) - Deng, Xiaoying; Anglin, Paul M.; Gao, Yanmin; Sun, Hua
Abstract: Business decisions made by the real estate industry have a profound effect on the well-being of people who live, work, or shop in these buildings. While these decisions may be informed by evidence, the available evidence is often incomplete or imperfect. Therefore, the personal opinions or judgments of senior executives can have an effect. In this paper, we study these effects in two parts: risk-taking and environmental, social, and governance (ESG) activities. Since a person's political learning is a relatively stable measure, and is associated with preferences for risk and ESG activities, we examine how the political leanings of the CEOs are related to these effects. Using the data from 2003 to 2016, we find that real estate investment trusts with Democratic-leaning CEOs tend to take more risks, as evidenced by higher levels of leverage and more risk in stock prices. We further find that Democratic-leaning CEOs are more broadly engaged in environmentally oriented ESG activities.